2012
DOI: 10.1002/clen.201100123
|View full text |Cite
|
Sign up to set email alerts
|

Water Quality Management Based on Division of Dry and Wet Seasons in Pearl River Delta, China

Abstract: In the Pearl River Delta (PRD), river water quality deteriorates continually due to the population increase and ongoing industrialization and urbanization. In this study, a water quality management paradigm based on the seasonal variation is proposed. For better exploring the seasonal change of water quality, wavelet analysis was used to analyze the division of dry and wet seasons in the PRD during 1952PRD during -2009. Then water quality seasonal variation in 2008 and relevant impact factors were analyzed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…For example, high COD concentration during the wet season was exhibited in Danjiangkou Reservoir, China (Li et al 2009) and in the Lake of the Francesa, Brazil (mean: 36.6 mg/L) (Kimura et al 2011). Inversely, high COD values during the dry season also have been observed in Semarang, Indonesia (Mangimbulude et al 2009); upper Ogun River in Nigeria (Adeogun et al 2011) and Pearl River Delta, China (Fan et al 2012). BOD concentrations were varied during both wet and dry seasons could be associated with organic loads in this area.…”
Section: Distribution and Diversity Of Aquatic Insects Communitymentioning
confidence: 62%
See 1 more Smart Citation
“…For example, high COD concentration during the wet season was exhibited in Danjiangkou Reservoir, China (Li et al 2009) and in the Lake of the Francesa, Brazil (mean: 36.6 mg/L) (Kimura et al 2011). Inversely, high COD values during the dry season also have been observed in Semarang, Indonesia (Mangimbulude et al 2009); upper Ogun River in Nigeria (Adeogun et al 2011) and Pearl River Delta, China (Fan et al 2012). BOD concentrations were varied during both wet and dry seasons could be associated with organic loads in this area.…”
Section: Distribution and Diversity Of Aquatic Insects Communitymentioning
confidence: 62%
“…It has been found that BOD has positive relationship with organic pollution such as domestic sewage (Islam et al 2012), therefore could indicate microbial activities in the water bodies (Nakamura et al 2007;Pant & Adholeya 2007). High level of BOD during the dry season also has been observed in Chini Lake, Malaysia (Islam et al 2012) and Pearl River Delta, China (Fan et al 2012) and Kathmandu Valley, Nepal (Rutkowski et al 2007). In comparison with other rivers in Malaysia, the WQI values for Juru River ranged from class III to class IV (Al-Shami et al 2011), Langat River (Azrina et al 2006), 53.6-81.9 (II-III) in the Linggi River (Ahmad et al 2002), 26.43-86.9 (II-V) in the Penang River (Maznah & Mansor 2002) and 47.59-54.35 (III-IV) in the Petani River (Hazzeman et al 2006).…”
Section: Distribution and Diversity Of Aquatic Insects Communitymentioning
confidence: 99%
“…Given seasonal differences, the unbalanced distribution of precipitation results in an apparent variation in surface runoff and further imbalance in the spatial distribution of hydro-chemical characteristics in the research zone [27][28][29]. Overall, hydro-chemical characteristic parameters changed significantly during rainy and dry seasons (Table 2).…”
Section: Characteristics Of Hydro-chemical Characteristicsmentioning
confidence: 99%
“…Evaluation of water quality can be conducted with spatial and temporal approach [1][2][3][4][5], [12], [20], [21]. Therefore, the availability of periodic and regular (time series) data monitoring is the success key in performing the water quality evaluation [14][15][16][17], [8], [9]. In addition to historical data series, the selection of appropriate water quality parameters is also a very important variable in evaluating the quality of water source [18], [20].…”
Section: Introductionmentioning
confidence: 99%